Ekoteologi Islam dalam Tafsir Sunda: Pendidikan Lingkungan Berbasis Kearifan Lokal dalam Tafsir Ayat Suci Lelenyepaneun - Dindin Moh Saepudin; Ela Sartika; Bunbun Muhamad Burhanudin (UIN Sunan Gunung Djati Bandung, 2026)
The global environmental crisis calls for an approach to religious education that is not only normative but also contextual and transformative. This article aims to examine the teaching of eco-theological verses in Sundanese exegesis through a study of Tafsir Ayat Suci Lelenyepaneun by Moh. E. Hasim, emphasizing the integration of the values of tawhid, nature, and local culture. This research employs a qualitative-descriptive approach using library research methods, as well as thematic analysis of Qur’anic verses related to ecology, specifically Surah al-Baqarah [2]: 30, Surah al-A‘rāf [7]: 56, and Surah ar-Rūm [30]: 41. The results of the study indicate that Hasim’s exegesis presents a theocentric, ecological, and ethical model of Islamic eco-theology through a Sundanese cultural approach. The concept of khalifah is understood as a divine trust that demands human responsibility in maintaining the balance of nature, while environmental degradation is interpreted as a moral and spiritual consequence of the misuse of the mandate of khalifah. By employing local language, cultural metaphors, and critiques of socio-ecological realities, The Tafsir Lelenyepaneun serves as an effective and contextual medium for environmental education. This article concludes that Moh. E. Hasim’s Sundanese exegesis functions not only as a work of local exegesis but also as a model of eco-theological education rooted in local culture—one that is relevant for addressing the global environmental crisis. The integration of the values of tawhid, nature, and local culture in this exegesis demonstrates the great potential of the Nusantara exegetical tradition to enrich the discourse of contemporary Islamic eco-theology.